A mechanical chemical polishing method for titanium alloy and titanium alloy polishing liquid
By using mechanical chemical polishing methods during the polishing process of titanium alloy, and using alumina abrasives of different morphology for coarse and fine polishing, the problem of difficult to take into account both the polishing speed, quality and service life in the prior art is solved, and efficient and high-quality polishing effect is achieved.
Patent Information
- Application Number
- CN202411629814.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing titanium alloy polishing methods are difficult to take into account both the polishing speed, polishing quality and service life, and there is a problem of missing the other.
Mechanical chemical polishing method is used to carry out coarse and fine polishing by different grinding particles (sheet alumina, spherical alumina and amorphous alumina) successively, and the polishing process is controlled to improve the polishing efficiency and quality.
The effects of high polishing speed, high polishing quality and long service life are achieved, and the problems that are difficult to take into account in the polishing process in the prior art are solved.
Smart Images

Figure CN119115672B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polishing, in particular to grinding and polishing of titanium alloys, and specifically to a mechanical chemical polishing method of titanium alloys and a titanium alloy polishing liquid. Background Art
[0002] Titanium alloy is an alloy metal with good acid and alkali resistance and mechanical strength that is significantly superior to stainless steel and aluminum alloy. In recent years, it has been widely used in electronic products such as mobile phones, smart watches, and VR glasses. As titanium alloys are used more and more widely in electronic products, higher requirements are placed on their processing quality and efficiency. Polishing is a commonly used method for processing titanium alloys. At present, grinding particles are often used to mechanically polish titanium alloys, or grinding particles are made into polishing liquids to perform mechanical chemical polishing on titanium alloys. Commonly used grinding particles include silicon dioxide and aluminum oxide particles. However, in current practice, the polishing method using these grinding particles is difficult to take into account the polishing speed, polishing quality, and service life, and there is an obvious problem of losing one thing while gaining another. Therefore, this field urgently needs to seek a polishing method that can take into account the polishing speed, polishing quality, and service life when grinding and polishing titanium alloys. Summary of the invention
[0003] The object of the present invention is to overcome one or more deficiencies in the prior art and to provide an improved method for polishing titanium alloys. The method adopts a mechanical chemical polishing method, uses different grinding particles to perform rough polishing and fine polishing in sequence, and controls the polishing process, so that the present invention can achieve high polishing speed, high polishing quality and long service life when mechanically polishing titanium alloys (accompanied by chemical polishing at the same time).
[0004] In order to achieve the above object, a technical solution adopted by the present invention is: a mechanical chemical polishing method for titanium alloy, the mechanical chemical polishing method comprising:
[0005] Step (1), grinding and polishing the titanium alloy using a flaky aluminum oxide rough polishing liquid to obtain a rough polished titanium alloy workpiece;
[0006] Step (2), grinding and polishing the roughly polished titanium alloy workpiece using a titanium alloy polishing liquid;
[0007] The titanium alloy polishing liquid comprises spherical aluminum oxide, flaky aluminum oxide and amorphous aluminum oxide, wherein the mass ratio of the spherical aluminum oxide, the flaky aluminum oxide and the amorphous aluminum oxide is 1:0.6-2.5:1-4; in the spherical aluminum oxide, α-alumina accounts for more than 99%; in the flaky aluminum oxide, α-alumina accounts for 75%-87%; in the amorphous aluminum oxide, α-alumina accounts for 85%-92%;
[0008] Wherein, both the step (1) and the step (2) use an oblique axis polishing machine, and the polishing time of the step (1) is controlled to be less than or equal to 60% of the polishing time of the step (2).
[0009] According to some preferred aspects of the present invention, the polishing time of step (1) is controlled to be less than or equal to 50% of the polishing time of step (2).
[0010] In some embodiments of the present invention, in the step (1) and the step (2), the polishing temperature of the grinding and polishing is controlled to be 15-35°C, for example, it can be carried out at 20-30°C.
[0011] According to some preferred aspects of the present invention, the grinding and polishing in step (1) is assisted by polishing with an LP-66 polyurethane polishing pad, such as that from Universal, USA.
[0012] According to some preferred aspects of the present invention, the grinding and polishing in step (2) uses polyurethane black damping cloth to assist in polishing.
[0013] According to some preferred aspects of the present invention, during the process of controlling the grinding and polishing, the polishing pressure of the step (1) is less than or equal to the polishing pressure of the step (2).
[0014] In some embodiments of the present invention, during the process of controlling the grinding and polishing, the polishing pressure in step (1) is 0.2-0.4 MPa, and the polishing pressure in step (2) is 0.3-0.5 MPa.
[0015] In some embodiments of the present invention, in the step (1) and the step (2), the polishing speed during the grinding and polishing process is controlled to be 700-900 rpm respectively.
[0016] According to some preferred aspects of the present invention, the flaky alumina rough polishing solution in step (1) contains flaky alumina with a median particle size of 3-8 μm.
[0017] In some embodiments of the present invention, the method for preparing the flaky alumina rough polishing liquid includes: mixing pseudo-boehmite and a mineralizer (for example, ammonium chloride, etc., accounting for 0.2%-1.5% of the mass content of the pseudo-boehmite), and then calcining at 1300-1400°C, monitoring its α-phase conversion rate until the α-phase conversion rate is greater than 97%, and then wet-milling the calcined material until the median particle size is 3-8μm to obtain flaky alumina slurry; mixing the flaky alumina slurry, selective water and a first auxiliary agent to obtain a flaky alumina rough polishing liquid.
[0018] Furthermore, the first auxiliary agent comprises a combination of one or more selected from aluminum nitrate, citric acid, sodium polycarboxylate, bentonite and a defoaming agent.
[0019] Furthermore, the defoaming agent may be a polysilane defoaming agent or the like.
[0020] Furthermore, in terms of mass percentage, in the flaky alumina rough polishing liquid, aluminum nitrate accounts for 1%-3%, citric acid accounts for 0.05%-0.6%, sodium polycarboxylate accounts for 0.2%-1.5%, bentonite accounts for 0.1%-1%, and defoaming agent accounts for 0.02%-0.5%.
[0021] According to some preferred aspects of the present invention, in the step (2), the median particle size of the spherical alumina, the median particle size of the flaky alumina and the median particle size of the amorphous alumina are each independently 0.8-2.0 μm.
[0022] According to some preferred aspects of the present invention, in the step (2), the absolute value of the difference between any two of the median particle size of the spherical alumina, the median particle size of the flaky alumina and the median particle size of the amorphous alumina is less than or equal to 0.15 μm.
[0023] Furthermore, in some embodiments of the present invention, in the step (2), the median particle size of the spherical alumina, the median particle size of the flaky alumina, and the median particle size of the amorphous alumina are each independently 1.0-1.6 μm.
[0024] According to some preferred aspects of the present invention, in the step (2), the mass ratio of the spherical alumina, the flaky alumina and the amorphous alumina is 1:0.8-1.5:1.5-4.
[0025] According to some preferred aspects of the present invention, in the step (2), in the titanium alloy polishing liquid, the spherical aluminum oxide accounts for 0.60%-1.75%, the flaky aluminum oxide accounts for 0.9%-1.75%, and the amorphous aluminum oxide accounts for 1.5%-2.8%, calculated by mass percentage.
[0026] According to some preferred aspects of the present invention, in step (2), the method for preparing the titanium alloy polishing liquid comprises: stirring and mixing the spherical alumina, the flaky alumina, and the amorphous alumina with a silane coupling agent respectively, and then mixing them with the second auxiliary agent.
[0027] According to some preferred and specific aspects of the present invention, during the preparation of the titanium alloy polishing liquid, the ratio of the total added mass of the spherical aluminum oxide, the flaky aluminum oxide and the amorphous aluminum oxide to the added mass of the silane coupling agent is 1:0.008-0.1.
[0028] According to some preferred and specific aspects of the present invention, during the preparation of the titanium alloy polishing liquid, the silane coupling agent accounts for 0.05%-0.5% in the titanium alloy polishing liquid in terms of mass percentage.
[0029] In the present invention, the aluminum oxide abrasive particles are pretreated with a silane coupling agent, which is beneficial to bridge the three aluminum oxide abrasives with the resin polishing pad and strengthen the grinding and cutting effect of the abrasive particles on the polishing pad. In some embodiments, the aluminum oxide abrasive particles can be treated with a silane coupling agent aqueous solution with a mass concentration of 10wt.%-15wt.%.
[0030] In some embodiments of the present invention, during the preparation of the titanium alloy polishing liquid, the temperature during the stirring and mixing process is controlled to be always less than or equal to 22°C.
[0031] In some embodiments of the present invention, the second auxiliary agent includes a combination of one or more selected from the group consisting of a dispersant, an oxidant, a lubricant, a suspending agent, a defoaming agent and a pH regulator.
[0032] According to some preferred and specific aspects of the present invention, the second auxiliary agent includes a dispersant, an oxidant, a lubricant, a suspending agent and a defoaming agent;
[0033] In terms of mass percentage, in the titanium alloy polishing liquid, the dispersant accounts for 0.2%-1.5%, the oxidant accounts for 1.0%-2.5%, the lubricant accounts for 0.5%-1.6%, the suspending agent accounts for 0.1%-2%, and the defoaming agent accounts for 0.01%-0.5%.
[0034] In some embodiments, in the titanium alloy polishing liquid, the dispersant may be a sodium salt of polycarboxylate.
[0035] In some embodiments, in the titanium alloy polishing liquid, the oxidant may be potassium persulfate.
[0036] In some embodiments, in the titanium alloy polishing liquid, the lubricant may be glycerol.
[0037] In some embodiments, in the titanium alloy polishing liquid, the suspending agent may be bentonite.
[0038] In some embodiments, in the titanium alloy polishing liquid, the defoaming agent may be a polysiloxane defoaming agent, for example, BYK-024 polysiloxane defoaming agent.
[0039] According to some specific aspects of the present invention, the pH adjuster is used to adjust the pH value of the titanium alloy polishing liquid to 3.5-7.5. In some embodiments, the pH adjuster can be selected from alkali metal hydroxides or their aqueous solutions, aluminum nitrate or their aqueous solutions, etc., and the alkali metal hydroxide can be sodium hydroxide, potassium hydroxide or their respective aqueous solutions.
[0040] According to some preferred aspects of the present invention, in the step (2), the preparation method of the spherical alumina comprises: mixing pseudo-boehmite, sulfuric acid and water into a slurry and then spraying granulating the spherical particles to obtain spherical particles, and then calcining the spherical particles at a calcination temperature of 1030-1200°C, monitoring the α-phase conversion rate until the α-phase conversion rate reaches more than 99%, and then wet ball milling the calcined material to obtain the spherical alumina.
[0041] In some embodiments, the method of preparing the spherical alumina comprises:
[0042] Pseudo-boehmite powder is added to deionized water, and then dilute sulfuric acid with a mass concentration of 10%-25% is added, stirred for 50-100 minutes, passed through a 50-70 mesh sieve, and then spray granulated. The parameters of spray granulation are: inlet temperature 260-300℃, outlet temperature: 110-130℃, and atomizing disk frequency 40-60Hz.
[0043] According to some preferred aspects of the present invention, in the step (2), the method for preparing the flaky alumina comprises: mixing pseudo-boehmite and / or aluminum hydroxide and a mineralizer, and then calcining them at 1020-1200°C, monitoring the α-phase conversion rate until the α-phase conversion rate reaches 75%-87%, and then wet-ball milling the calcined material to obtain the flaky alumina.
[0044] Furthermore, the mineralizer comprises ammonium chloride; and / or, in terms of mass percentage, the amount of the mineralizer added accounts for 0.4%-1.0% of the amount of the pseudo-boehmite and / or aluminum hydroxide added.
[0045] According to some preferred aspects of the present invention, in the step (2), the method for preparing the amorphous alumina comprises: calcining pseudo-boehmite and / or aluminum hydroxide at 1050-1250°C, monitoring the α-phase conversion rate until the α-phase conversion rate reaches 85%-92%, and then wet-ball milling the calcined material to obtain the amorphous alumina.
[0046] In some embodiments of the present invention, in step (2), the method for preparing the titanium alloy polishing liquid comprises:
[0047] (1) Pseudo-boehmite powder is added to water, and then diluted sulfuric acid with a mass concentration of 10%-25% is added to prepare a slurry, and then spray granulation is performed to obtain spherical particles with a median particle size of 30-80 μm; wherein, in terms of mass percentage, the pseudo-boehmite powder accounts for 40%-50%, water accounts for 49%-59%, and the diluted sulfuric acid accounts for 0.1%-1.0% in the prepared slurry;
[0048] The spherical particles are calcined at a calcination temperature of 1030-1200° C., and the α-phase conversion rate is monitored until the α-phase conversion rate reaches more than 99%. The calcined material is then wet-milled to a median particle size of 0.8-2.0 μm to obtain a spherical alumina slurry with a solid content of 30%-40%;
[0049] Pseudo-boehmite and / or aluminum hydroxide and a mineralizer are mixed, and then calcined at 1020-1200° C., and the α-phase conversion rate is monitored until the α-phase conversion rate reaches 75%-87%, and then the calcined material is wet-milled to a median particle size of 0.8-2.0 μm to obtain a flaky alumina slurry with a solid content of 30%-40%;
[0050] The pseudo-boehmite and / or aluminum hydroxide is calcined at 1050-1250° C., and the α-phase conversion rate thereof is monitored until the α-phase conversion rate reaches 85%-92%. The calcined material is then wet-milled to a median particle size of 0.8-2.0 μm to obtain an amorphous aluminum oxide slurry having a solid content of 30%-40%;
[0051] (2) mixing and stirring a spherical alumina slurry with a solid content of 30%-40%, a flaky alumina slurry with a solid content of 30%-40%, and an amorphous alumina slurry with a solid content of 30%-40%, adding a silane coupling agent aqueous solution with a mass concentration of 10%-25%, and stirring to obtain a pretreated abrasive slurry; wherein the slurry temperature is kept less than or equal to 22° C. during the stirring process, and the silane coupling agent aqueous solution is obtained by dispersing a silane coupling agent in water;
[0052] (3) The pretreated abrasive slurry, water and the second auxiliary agent are mixed according to the formula, and the pH value of the system is adjusted to 3.5-7.5 using a pH adjuster to obtain the titanium alloy polishing liquid.
[0053] In some embodiments, the water may be deionized water.
[0054] In some embodiments, the wet ball milling in the present invention uses spherical zirconium beads with a diameter of 2-4 mm.
[0055] Another technical solution provided by the present invention is: a titanium alloy polishing liquid, which comprises an abrasive and a second auxiliary agent, wherein the abrasive is composed of spherical aluminum oxide, flaky aluminum oxide and amorphous aluminum oxide;
[0056] In the spherical alumina, α-alumina accounts for more than 99%;
[0057] In the flaky aluminum oxide, α-alumina accounts for 75%-87%;
[0058] In the amorphous alumina, α-alumina accounts for 85%-92%;
[0059] The feed mass ratio of the spherical alumina, the flaky alumina and the amorphous alumina is 1:0.6-2.5:1-4.
[0060] Further, the titanium alloy polishing liquid comprises, in terms of mass percentage, 0.60%-1.75% of spherical alumina, 0.9%-1.75% of flaky alumina, 1.5%-2.8% of amorphous alumina, 0.05%-0.5% of a silane coupling agent, 0.2%-1.5% of a dispersant, 1.0%-2.5% of an oxidant, 0.5%-1.6% of a lubricant, 0.1%-2% of a suspending agent, 0.01%-0.5% of a defoaming agent, and 50%-76% of water;
[0061] The titanium alloy polishing liquid further comprises a pH value adjuster for adjusting the pH value of the titanium alloy polishing liquid to 3.5-7.5.
[0062] Another technical solution provided by the present invention is a mechanical chemical polishing method of titanium alloy, the polishing method comprising: a process of polishing the titanium alloy with a titanium alloy polishing liquid and a process of preparing the titanium alloy polishing liquid;
[0063] The process of preparing the titanium alloy polishing liquid comprises: preparing spherical aluminum oxide, flaky aluminum oxide and amorphous aluminum oxide respectively, and mixing the spherical aluminum oxide, the flaky aluminum oxide, the amorphous aluminum oxide and a second auxiliary agent;
[0064] Wherein, α-alumina accounts for more than 99% of the spherical alumina;
[0065] In the flaky aluminum oxide, α-alumina accounts for 75%-87%;
[0066] In the amorphous alumina, α-alumina accounts for 85%-92%;
[0067] The feed mass ratio of the spherical alumina, the flaky alumina and the amorphous alumina is 1:0.6-2.5:1-4.
[0068] In the present invention, "amorphous aluminum oxide" refers to aluminum oxide having an irregular morphology.
[0069] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0070] Based on the problem of neglecting one thing while focusing on another in the existing process of polishing titanium alloy, the present invention innovatively provides an improved polishing method, which adopts a mechanical chemical polishing method, performs rough polishing and fine polishing in sequence with different grinding particles, and controls the polishing process, so that the present invention can achieve high polishing speed, high polishing quality and long service life when mechanically polishing titanium alloy (accompanied by chemical polishing at the same time);
[0071] Specifically, in the present invention, the mechanical chemical polishing method of the present invention can greatly shorten the polishing time of rough polishing, and a large-size flaky aluminum oxide rough polishing liquid can be selected, which not only improves the polishing speed of the titanium alloy, but also simplifies the grinding time in the preparation process of the rough polishing liquid, thereby improving work efficiency; in particular, on the basis of reducing the polishing time as a whole, the present invention also obtains excellent polishing quality, thereby solving the problem of losing one thing while gaining another in the prior art.
[0072] In addition, the titanium alloy polishing liquid of the present invention uses a polishing liquid containing a specific composite abrasive system, and the composite abrasive system is composed of three types of aluminum oxide morphologies. Practice has shown that when the α-phase conversion rate of aluminum oxides with different morphologies is further controlled, that is, the proportion of α-aluminum oxide in aluminum oxides with different morphologies is controlled, and the mutual ratio of the three types of aluminum oxide morphologies is controlled at the same time, not only the difference in cutting force between aluminum oxides with different morphologies is adjusted and balanced, but also the problem of uneven cutting that may be caused by abrasives with different morphologies during the polishing process is avoided. It further ensures that after polishing the titanium alloy using the method of the present invention, excellent surface quality is obtained, the surface roughness is low, the surface gloss is high, and the service life of the polishing liquid is unexpectedly improved. That is, the present invention greatly extends the polishing life of a single batch of polishing liquid, thereby reducing the frequency of replacing the polishing liquid and significantly reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 This is a morphology diagram of the material after calcination during the preparation of spherical alumina slurry in Example 1;
[0074] Figure 2 This is a morphology diagram of the material after calcination during the preparation of flaky alumina slurry in Example 1;
[0075] Figure 3 This is a morphology diagram of the material after calcination during the preparation of amorphous alumina slurry in Example 1;
[0076] Figure 4This is a metallographic microscope image of the titanium alloy before polishing in Application Example 1;
[0077] Figure 5 This is a metallographic microscope image of the polished titanium alloy in Application Example 1;
[0078] Figure 6 This is a metallographic microscope image of the polished titanium alloy in Application Example 2;
[0079] Figure 7 This is a metallographic microscope image of the polished titanium alloy in Application Example 3;
[0080] Figure 8 This is a metallographic microscope image of the polished titanium alloy in Comparative Example 1;
[0081] Fig. 9 The metallographic microscope image of the polished titanium alloy in Comparative Example 2 is shown;
[0082] Fig.10 The metallographic microscope image of the polished titanium alloy in Comparative Example 3 is shown;
[0083] Fig.11 The metallographic microscope image of the polished titanium alloy in Comparative Example 4 is shown;
[0084] Fig.12 This is a metallographic microscope image of the polished titanium alloy in Comparative Example 5;
[0085] Fig.13 The life polishing curve of the titanium alloy polishing liquid prepared in Application Example 1;
[0086] Fig.14 The life polishing curve of the titanium alloy polishing liquid prepared in Application Example 2;
[0087] Fig.15 The life polishing curve of the titanium alloy polishing liquid prepared in Application Example 3;
[0088] Fig.16 The life polishing curve of the titanium alloy polishing liquid prepared in Comparative Example 5;
[0089] Fig.17 This is a metallographic microscope image of the titanium alloy before polishing in Application Example 4 (corresponding to the method using coarse polishing liquid A);
[0090] Fig.18 This is a metallographic microscope image of the titanium alloy before polishing in Application Example 4 (corresponding to the method using coarse polishing liquid B);
[0091] Fig.19 This is a metallographic microscope image of the polished titanium alloy in Application Example 4 (corresponding to the method using coarse polishing liquid A);
[0092] Fig. 20 This is a metallographic microscope image of the polished titanium alloy in Application Example 4 (corresponding to the method using coarse polishing liquid B);
[0093] Fig.21 This is a metallographic microscope image of the titanium alloy before polishing in Comparative Example 6 (corresponding to the method using coarse polishing liquid A);
[0094] Fig. 22 This is a metallographic microscope image of the titanium alloy before polishing in Comparative Example 6 (corresponding to the method using coarse polishing liquid B);
[0095] Fig.23 This is a metallographic microscope image of the titanium alloy after polishing in Comparative Example 6 (corresponding to the method using coarse polishing liquid A);
[0096] Fig.24 This is a metallographic microscope image of the titanium alloy after polishing in Comparative Example 6 (corresponding to the method using coarse polishing liquid B). DETAILED DESCRIPTION
[0097] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.
[0098] Unless otherwise specified in the following embodiments, all raw materials are purchased from commercial sources or prepared by conventional methods in the art. In the following, "%" is a mass percentage, "aqueous solution of silane coupling agent KH-550 with a mass concentration of 0.8%" is prepared by dispersing silane coupling agent KH-550 in water, "aqueous solution of bentonite with a mass concentration of 8%" is prepared by dispersing bentonite in water, bentonite is purchased from Aladdin, and ordinary pseudo-boehmite has a large difference in the content of each batch of commercial sources, so the actual measured index is used; in addition, the potassium hydroxide aqueous solution or aluminum nitrate aqueous solution used to adjust the pH value of the system can be ignored due to the small amount added and is not included in the total amount.
[0099] Embodiment 1:
[0100] This example provides a method for preparing a titanium alloy polishing liquid and the titanium alloy polishing liquid prepared therefrom. The method for preparing the titanium alloy polishing liquid comprises:
[0101] (1) Add powder of common pseudo-boehmite (purchased from Aladdin, with measured Na content of 134 ppm and Si content of 175 ppm) into deionized water, and then add dilute sulfuric acid with a mass concentration of 20% to prepare a slurry (wherein, in terms of mass percentage, the common pseudo-boehmite accounts for 45%, the deionized water accounts for 54.5%, and the dilute sulfuric acid accounts for 0.5%), and then spray granulate (the process parameters of spray granulation are inlet temperature of 280°C, outlet temperature of 120°C, and atomizing disk frequency of 50 Hz) to obtain spherical particles with smooth surface (the measured median particle size is about 47.2 μm), and then calcine the spherical particles at a calcination temperature of 1130°C, and monitor the α-phase conversion rate until the α-phase conversion rate reaches 100%. The morphology of the calcined material is shown in FIG. Figure 1 As shown, the calcined material was then wet-milled (milling beads: spherical zirconium beads, with a diameter of about 3 mm), and the median particle size after ball milling was measured to be about 1.28 μm, obtaining a spherical alumina slurry with a solid content of about 33.7%;
[0102] Ordinary pseudo-boehmite (purchased from Aladdin, measured: Na content: 134ppm, Si content: 175ppm) and ammonium chloride (in terms of mass percentage, the added mass of ammonium chloride is 0.7% of the ordinary pseudo-boehmite) were mixed, and then calcined at 1020°C, and the α-phase conversion rate was monitored until the α-phase conversion rate reached 82%. The morphology of the calcined material can be found in Figure 2 As shown, the calcined material was then wet-milled (milling beads: spherical zirconium beads, with a diameter of about 3 mm), and the median particle size after ball milling was measured to be about 1.19 μm, obtaining a flaky alumina slurry with a solid content of about 32.9%;
[0103] Ordinary pseudo-boehmite (purchased from Aladdin, measured: Na content: 134ppm, Si content: 175ppm) was selected as the raw material and calcined at 1180°C. The α-phase conversion rate was monitored until the α-phase conversion rate reached 91%. The morphology of the calcined material can be found in Figure 3 As shown, the calcined material was then wet-milled (milling beads: spherical zirconium beads, with a diameter of about 3 mm), and the median particle size after ball milling was measured to be about 1.26 μm, obtaining an amorphous alumina slurry with a solid content of about 33.1%;
[0104] (2) 3% (by mass content of the polishing liquid) of spherical alumina slurry, 3% (by mass content of the polishing liquid) of flaky alumina slurry and 6.5% (by mass content of the polishing liquid) of amorphous alumina slurry prepared according to the above method are mixed and stirred, and a silane coupling agent KH-550 aqueous solution with a mass content of 13% and a mass concentration of 0.8% of the polishing liquid is added, and stirred for 30 minutes. During the stirring process, a cooling stirring tank is used to keep the slurry temperature below 22° C. After the stirring is completed, a pretreated abrasive slurry is obtained;
[0105] (3) According to the formula, the above-mentioned pretreated abrasive slurry is transferred to a stirring tank at room temperature, and deionized water accounting for 65.5% of the mass content of the polishing liquid is added, and stirred for 20 minutes; polycarboxylate sodium salt SOLSPERSE-24000 accounting for 1.2% of the mass content of the polishing liquid is added, and stirred for 10 minutes; then potassium persulfate accounting for 1.6% of the mass content of the polishing liquid is added, and stirred for 10 minutes; propylene glycol accounting for 1.1% of the mass content of the polishing liquid is added, and stirred for 20 minutes; then bentonite aqueous solution accounting for 5% of the mass content of the polishing liquid and having a mass concentration of 8% is added, and stirred for 10 minutes; then polyoxysilane defoamer BYK-024 accounting for 0.1% of the mass content of the polishing liquid is added, and stirred for 5 minutes, and finally the pH value of the system is adjusted to 7±0.5 with a potassium hydroxide aqueous solution having a mass concentration of 10%, to obtain the titanium alloy polishing liquid.
[0106] Embodiment 2:
[0107] This example provides a method for preparing a titanium alloy polishing liquid and the titanium alloy polishing liquid prepared therefrom. The method for preparing the titanium alloy polishing liquid comprises:
[0108] (1) Add powder of common pseudo-boehmite (purchased from Aladdin, measured: Na content: 184ppm, Si content: 239ppm) into deionized water, and then add dilute sulfuric acid with a mass concentration of 20% to prepare a slurry (wherein, in terms of mass percentage, the common pseudo-boehmite accounts for 45%, deionized water accounts for 54.5%, and dilute sulfuric acid accounts for 0.5%), and then spray granulate (the process parameters of spray granulation are: inlet temperature 280°C, outlet temperature: 1 20°C, atomizing disk frequency 50Hz), to obtain spherical particles with smooth surface (measured median particle size of about 56.8μm), then calcined the spherical particles at a calcination temperature of 1150°C, monitored the α-phase conversion rate until the α-phase conversion rate reached 100%, then wet ball milled the calcined material (milling beads: spherical zirconium beads, diameter of about 3mm), measured the median particle size after ball milling to be about 1.21μm, and obtained a spherical alumina slurry with a solid content of about 34.1%;
[0109] High-purity aluminum hydroxide (purchased from Aladdin, with a purity of 99.99%) and ammonium chloride (in terms of mass percentage, the added mass of ammonium chloride is 0.7% of the high-purity aluminum hydroxide) are mixed, and then calcined at 1020°C, and the α-phase conversion rate is monitored until the α-phase conversion rate reaches 86%. The calcined material is then wet-milled (milling beads: spherical zirconium beads, with a diameter of about 3 mm), and the median particle size after ball milling is measured to be about 1.23 μm, thereby obtaining a flaky aluminum oxide slurry with a solid content of about 31.7%;
[0110] High-purity aluminum hydroxide (purchased from Aladdin, with a purity of 99.99%) was selected as a raw material, and calcined at 1200°C. The α-phase conversion rate was monitored until the α-phase conversion rate reached 89%. The calcined material was then wet-milled (milling beads: spherical zirconium beads, with a diameter of about 3 mm). The median particle size after ball milling was measured to be about 1.17 μm, and an amorphous aluminum oxide slurry with a solid content of about 32.3% was obtained.
[0111] (2) 3.5% (by mass content of the polishing liquid) of spherical alumina slurry, 3.8% (by mass content of the polishing liquid) of flaky alumina slurry and 7.7% (by mass content of the polishing liquid) of amorphous alumina slurry prepared according to the above method are mixed and stirred, and a silane coupling agent KH-550 aqueous solution with a mass content of 10% and a mass concentration of 0.8% of the polishing liquid is added, and stirred for 30 minutes. During the stirring process, a cooling stirring tank is used to keep the slurry temperature below 22° C. After the stirring is completed, a pretreated abrasive slurry is obtained;
[0112] (3) According to the formula, the above-mentioned pretreated abrasive slurry is transferred to a stirring tank at room temperature, and deionized water accounting for 63.0% of the mass content of the polishing liquid is added, and stirred for 20 minutes; polycarboxylate sodium salt SOLSPERSE-24000 accounting for 1.2% of the mass content of the polishing liquid is added, and stirred for 10 minutes; potassium persulfate accounting for 2.0% of the mass content of the polishing liquid is added, and stirred for 10 minutes; propylene glycol accounting for 0.7% of the mass content of the polishing liquid is added, and stirred for 20 minutes; bentonite aqueous solution accounting for 8% of the mass content of the polishing liquid and having a mass concentration of 5% is added, and stirred for 10 minutes; polysiloxane defoamer BYK-024 accounting for 0.1% of the mass content of the polishing liquid is added, and stirred for 5 minutes. Finally, the pH value of the system is adjusted to 3.8±0.2 with an aluminum nitrate aqueous solution having a mass concentration of 10%, and the titanium alloy polishing liquid is obtained.
[0113] Embodiment 3:
[0114] This example provides a method for preparing a titanium alloy polishing liquid and the titanium alloy polishing liquid prepared therefrom. The method for preparing the titanium alloy polishing liquid comprises:
[0115] (1) Add ordinary pseudo-boehmite (purchased from Aladdin, measured: Na content: 209ppm, Si content: 276ppm) powder into deionized water, and then add dilute sulfuric acid with a mass concentration of 20% to prepare a slurry (wherein, in terms of mass percentage, ordinary pseudo-boehmite accounts for 45%, deionized water accounts for 54.5%, and dilute sulfuric acid accounts for 0.5%), and then spray granulate (the process parameters of spray granulation are: inlet temperature 260°C, outlet temperature: 1 20°C, atomizing disk frequency 50Hz), to obtain spherical particles with smooth surface (measured median particle size of about 60.7μm), then calcined the spherical particles at a calcination temperature of 1170°C, monitored the α-phase conversion rate until the α-phase conversion rate reached 100%, then wet ball milled the calcined material (milling beads: spherical zirconium beads, diameter of about 3mm), measured the median particle size after ball milling to be about 1.17μm, and obtained a spherical alumina slurry with a solid content of about 33.5%;
[0116] Ordinary pseudo-boehmite (purchased from Aladdin, measured: Na content: 209ppm, Si content: 276ppm) and ammonium chloride (in terms of mass percentage, the added mass of ammonium chloride is 0.7% of the ordinary pseudo-boehmite) are mixed, and then calcined at 1035°C, and the α-phase conversion rate is monitored until the α-phase conversion rate reaches 86%, and then the calcined material is wet-milled (milling beads: spherical zirconium beads, with a diameter of about 3mm), and the median particle size after ball milling is measured to be about 1.25μm, to obtain a flaky alumina slurry with a solid content of about 33.9%;
[0117] High-purity aluminum hydroxide (purchased from Aladdin, with a purity of 99.99%) was selected as a raw material, and calcined at 1090°C, and its α-phase conversion rate was monitored until the α-phase conversion rate reached 89%. The calcined material was then wet-milled (milling beads: spherical zirconium beads, with a diameter of about 3 mm), and the median particle size after ball milling was measured to be about 1.22 μm, obtaining an amorphous aluminum oxide slurry with a solid content of about 34.6%;
[0118] (2) 3.3% (by mass content of the polishing liquid) of spherical alumina slurry, 3.0% (by mass content of the polishing liquid) of flaky alumina slurry and 6.4% (by mass content of the polishing liquid) of amorphous alumina slurry prepared according to the above method were mixed and stirred, and a silane coupling agent KH-550 aqueous solution with a mass content of 11% and a mass concentration of 0.8% of the polishing liquid was added, and stirred for 30 minutes. During the stirring process, a cooling stirring tank was used to keep the slurry temperature below 22° C. After the stirring was completed, a pretreated abrasive slurry was obtained;
[0119] (3) According to the formula, the above-mentioned pretreated abrasive slurry is transferred to a stirring tank at room temperature, and deionized water accounting for 67.0% of the mass content of the polishing liquid is added, and stirred for 20 minutes; polycarboxylate sodium salt SOLSPERSE-24000 accounting for 1.5% of the mass content of the polishing liquid is added, and stirred for 10 minutes; potassium persulfate accounting for 1.8% of the mass content of the polishing liquid is added, and stirred for 10 minutes; propylene glycol accounting for 0.9% of the mass content of the polishing liquid is added, and stirred for 20 minutes; bentonite aqueous solution accounting for 5% of the mass content of the polishing liquid and having a mass concentration of 8% is added, and stirred for 10 minutes; polyoxysilane defoamer BYK-024 accounting for 0.1% of the mass content of the polishing liquid is added, and stirred for 5 minutes. Finally, the pH value of the system is adjusted to 4.5±0.5 with an aluminum nitrate aqueous solution having a mass concentration of 10%, and the titanium alloy polishing liquid is obtained.
[0120] Embodiment 4:
[0121] This example provides a method for preparing a titanium alloy polishing liquid and the titanium alloy polishing liquid prepared therefrom. The method for preparing the titanium alloy polishing liquid comprises:
[0122] (1) Add ordinary pseudo-boehmite (purchased from Aladdin, measured: Na content: 264ppm, Si content: 394ppm) powder into deionized water, and then add dilute sulfuric acid with a mass concentration of 20% to prepare a slurry (wherein, in terms of mass percentage, ordinary pseudo-boehmite accounts for 45%, deionized water accounts for 54.5%, and dilute sulfuric acid accounts for 0.5%), and then spray granulate (the process parameters of spray granulation are inlet temperature 280℃, outlet temperature: 120℃, atomization The spherical particles were calcined at a temperature of 1130°C, and the α-phase conversion rate was monitored during the calcination process until the α-phase conversion rate reached 100%. The calcined material was wet-milled (milling beads: spherical zirconium beads, with a diameter of about 3 mm), and the median particle size after ball milling was measured to be about 1.20 μm, thereby obtaining a spherical alumina slurry with a solid content of about 35.1%;
[0123] Ordinary pseudo-boehmite (purchased from Aladdin, measured: Na content: 264ppm, Si content: 394ppm) and ammonium chloride (in terms of mass percentage, the added mass of ammonium chloride is 0.7% of the ordinary pseudo-boehmite) are mixed, and then calcined at 1025°C, and its α-phase conversion rate is monitored during the calcination process until the α-phase conversion rate reaches 85%, and then the calcined material is wet-milled (milling beads: spherical zirconium beads, with a diameter of about 3mm), and the median particle size after ball milling is measured to be about 1.15μm, to obtain a flaky alumina slurry with a solid content of about 34.4%;
[0124] Ordinary pseudo-boehmite (purchased from Aladdin, with measured Na content of 264ppm and Si content of 394ppm) was selected as a raw material, and calcined at 1200°C. During the calcination process, the α-phase conversion rate was monitored until the α-phase conversion rate reached 90%. The calcined material was then wet-milled (milling beads: spherical zirconium beads with a diameter of about 3mm). The median particle size after ball milling was measured to be about 1.13μm, and an amorphous alumina slurry with a solid content of about 32.3% was obtained.
[0125] (2) 3% (by mass content of the polishing liquid) of spherical alumina slurry, 3% (by mass content of the polishing liquid) of flaky alumina slurry and 6.5% (by mass content of the polishing liquid) of amorphous alumina slurry prepared according to the above method were mixed and stirred, and a silane coupling agent KH-550 aqueous solution with a mass content of 13% and a mass concentration of 0.8% in the polishing liquid was added, and stirred for 30 minutes. During the stirring process, a cooling stirring tank was used to keep the slurry temperature below 22° C. After the stirring was completed, a pretreated abrasive slurry was obtained;
[0126] (3) According to the formula, the above-mentioned pretreated abrasive slurry is transferred to a stirring tank at room temperature, and deionized water accounting for 65.5% of the mass content of the polishing liquid is added, and stirred for 20 minutes; polycarboxylate sodium salt SOLSPERSE-24000 accounting for 1.2% of the mass content of the polishing liquid is added, and stirred for 10 minutes; potassium persulfate accounting for 1.6% of the mass content of the polishing liquid is added, and stirred for 10 minutes; propylene glycol accounting for 1.1% of the mass content of the polishing liquid is added, and stirred for 20 minutes; bentonite aqueous solution accounting for 5% of the mass content of the polishing liquid and having a mass concentration of 8% is added, and stirred for 10 minutes; polyoxysilane defoamer BYK-024 accounting for 0.1% of the mass content of the polishing liquid is added, and stirred for 5 minutes. Finally, the pH value of the system is adjusted to 7±0.5 with an aluminum nitrate aqueous solution having a mass concentration of 10%, and the titanium alloy polishing liquid is obtained.
[0127] Comparative Example 1:
[0128] The method is basically the same as Example 1, except that the three types of alumina morphologies are replaced by a single flaky alumina with the same added mass.
[0129] Comparative Example 2:
[0130] It is basically the same as Example 1, with the only difference being that among the three types of alumina morphologies, amorphous alumina is not added, and is replaced by spherical alumina of equal added mass, that is, the addition amount of flake alumina is 1% (about 3% of flake alumina slurry), and the addition amount of spherical alumina is 3.1% (about 9.2% of spherical alumina slurry), and the addition amount of deionized water is adaptively adjusted.
[0131] Comparative Example 3:
[0132] It is basically the same as Example 1, except that the α-phase conversion rate of the alumina with three morphologies is 100%.
[0133] Comparative Example 4:
[0134] The method is basically the same as Example 1, with the only difference being that the mass ratio of the spherical alumina, the flaky alumina and the amorphous alumina is controlled to be 1:2:6, that is, the mass percentage of the spherical alumina in the polishing liquid is controlled to be 1% (corresponding to about 3% of the spherical alumina slurry), the mass percentage of the flaky alumina in the polishing liquid is controlled to be 2% (corresponding to about 6% of the flaky alumina slurry), and the mass percentage of the amorphous alumina in the polishing liquid is controlled to be 6% (corresponding to about 18% of the amorphous alumina slurry).
[0135] Comparative Example 5:
[0136] It is basically the same as Example 1, except that the three types of alumina morphologies are replaced by a single spherical alumina with the same added mass.
[0137] Comparative Example 6:
[0138] It is basically the same as Example 1, except that the three types of aluminum oxide morphologies are replaced by a single amorphous aluminum oxide with the same added mass.
[0139] Application Example 1:
[0140] This example provides a mechanical chemical polishing method for titanium alloy, the mechanical chemical polishing method comprising:
[0141] Step (1), grinding and polishing the titanium alloy using a flaky aluminum oxide rough polishing liquid to obtain a rough polished titanium alloy workpiece;
[0142] The titanium alloy is titanium alloy TC4 material;
[0143] The flaky alumina rough polishing liquid used was prepared by the following method: pseudo-boehmite (purchased from Aladdin, measured: Na content: 134ppm, Si content: 175ppm) and ammonium chloride (in terms of mass percentage, the added mass of ammonium chloride is 0.7% of ordinary pseudo-boehmite) were mixed, and then calcined at 1350°C, and its α-phase conversion rate was monitored until the α-phase conversion rate was greater than 97%, and then the calcined material was wet-milled (milling beads: spherical zirconium beads, with a diameter of about 3mm) until the median particle size D50 was about 3.8-3.9μm, D97≤12.00 μm, to obtain a flaky alumina slurry with a solid content of about 35%; dilute the flaky alumina slurry to a solid content of 20%, add 1.9% aluminum nitrate accounting for the mass content of the polishing liquid, then add 0.2% citric acid accounting for the mass content of the polishing liquid, then add 0.6% polycarboxylate sodium salt SOLSPERSE-24000 accounting for the mass content of the polishing liquid, then add 5% of the mass content of the polishing liquid and a bentonite aqueous solution with a mass concentration of 8%, and stir for 10 minutes; then add 0.1% of the mass content of the polishing liquid polyoxysilane defoamer BYK-024, stir to obtain a flaky alumina rough polishing liquid;
[0144] The polishing liquid temperature was 25°C. During the rough polishing process, an oblique axis single-side polishing machine (model JPX012.2A) was used with a 5-inch American Global LP-66 polyurethane polishing pad to polish the titanium alloy TC4 material. The polishing parameters were: polishing speed 800 rpm, polishing time 90 s, and polishing pressure 0.3.MPa.
[0145] Step (2), grinding and polishing the roughly polished titanium alloy workpiece using a titanium alloy polishing liquid;
[0146] The titanium alloy polishing liquid prepared in Example 1 is used;
[0147] The polishing liquid temperature was 25°C; during the polishing process, an oblique axis polishing machine (model JPX012.2A) was used with a 5-inch polyurethane black damping cloth to polish the titanium alloy TC4 material. The polishing parameters were: polishing speed: 800 rpm, polishing time: 180 s, and polishing pressure: 0.4 MPa.
[0148] Record the average removal amount, surface roughness, surface gloss and visual surface quality.
[0149] Calculation of average removal: Weigh the titanium alloy before and after polishing and calculate the difference, which indicates the strength of the polishing fluid cutting force.
[0150] Surface roughness measurement: measured using a TR-220 handheld surface roughness tester.
[0151] Surface gloss measurement: measured using a BYK AG-4446 60° gloss meter.
[0152] Metallographic microscope image of titanium alloy before polishing Figure 4 As shown, the metallographic microscope image of the polished titanium alloy is as follows Figure 5 shown.
[0153] The average removal during the first polishing was measured to be 35 mg / 180 s; the surface quality is shown in Figure 5 As shown, it presents a mirror effect when observed with the naked eye, and there are no obvious scratches under microscopic observation, and the surface quality meets the standards; the surface roughness is 0.013μm and the surface gloss is 792.3GU.
[0154] The service life of the titanium alloy polishing liquid used in the polishing method was further tested, as shown in Table 1.
[0155] Application Example 2:
[0156] The method is basically the same as Application Example 1, except that the titanium alloy polishing liquid prepared in Example 2 is used to polish the roughly polished titanium alloy workpiece.
[0157] The metallographic microscope image of the polished titanium alloy is as follows: Figure 6 shown.
[0158] The average removal during the first polishing was measured to be 55 mg / 180 s; the surface quality is shown in Figure 6 As shown, it presents a mirror effect when observed with the naked eye, and there are very few tiny scratches under microscopic observation, which have no obvious effect on the surface quality, and the surface quality meets the standard; the surface roughness is 0.023μm, and the surface gloss is 683.3GU.
[0159] The service life of the titanium alloy polishing liquid used in the polishing method was further tested, as shown in Table 1.
[0160] Application Example 3:
[0161] The method is basically the same as Application Example 1, except that the titanium alloy polishing liquid prepared in Example 3 is used to polish the roughly polished titanium alloy workpiece.
[0162] The metallographic microscope image of the polished titanium alloy is as follows: Figure 7 shown.
[0163] The average removal during the first polishing was measured to be 46 mg / 180 s; the surface quality is shown in Figure 7 As shown, it appears mirror-like when observed with the naked eye, and there are no obvious scratches under microscopic observation, and the surface quality meets the standards; the surface roughness is 0.025μm and the surface gloss is 680.7GU.
[0164] The service life of the titanium alloy polishing liquid used in the polishing method was further tested, as shown in Table 1.
[0165] Application Comparative Example 1:
[0166] The method is basically the same as Application Example 1, except that the titanium alloy polishing liquid prepared in Comparative Example 1 is used to polish the roughly polished titanium alloy workpiece.
[0167] The metallographic microscope image of the polished titanium alloy is as follows: Figure 8 shown.
[0168] The average removal during the first polishing was measured to be 41 mg / 180 s; the surface quality is shown in Figure 8 As shown, the naked eye observation shows a mirror effect with obvious scratches, and microscopic observation shows a large number of scratches, which have a serious impact on the surface quality and the surface quality does not meet the standards; the surface roughness is 0.136μm and the surface gloss is 661.4GU.
[0169] Application Comparative Example 2:
[0170] The method is basically the same as Application Example 1, except that the titanium alloy polishing liquid prepared in Comparative Example 2 is used to polish the roughly polished titanium alloy workpiece.
[0171] The metallographic microscope image of the polished titanium alloy is as follows: Fig. 9 shown.
[0172] The average removal during the first polishing was measured to be 21 mg / 180 s; the surface quality is shown in Fig. 9 As shown, it appears to have a scratched mirror effect when observed with the naked eye, and there are many scratches when observed under a microscope. The scratches have a more obvious impact on the surface quality, and the surface quality does not meet the standard; the surface roughness is 0.096μm and the surface gloss is 715.9GU.
[0173] Application Comparative Example 3:
[0174] The method is basically the same as Application Example 1, except that the titanium alloy polishing liquid prepared in Comparative Example 3 is used to polish the roughly polished titanium alloy workpiece.
[0175] The metallographic microscope image of the polished titanium alloy is as follows: Fig.10 shown.
[0176] The average removal during the first polishing was measured to be 46 mg / 180 s; the surface quality is shown in Fig.10 As shown, it appears to have a scratched mirror effect when observed with the naked eye, and deeper scratches are found under microscopic observation. The scratches have a serious impact on the surface quality, and the surface quality does not meet the standard; the surface roughness is 0.129μm and the surface gloss is 661.3GU.
[0177] Application Comparative Example 4:
[0178] The method is basically the same as Application Example 1, except that the titanium alloy polishing liquid prepared in Comparative Example 4 is used to polish the roughly polished titanium alloy workpiece.
[0179] The metallographic microscope image of the polished titanium alloy is as follows: Fig.11 shown.
[0180] The average removal during the first polishing was measured to be 36 mg / 180 s; the surface quality is shown in Fig.11 As shown, the naked eye observation shows a mirror effect with white spots, and microscopic observation shows obvious large white spots, which have a great influence on the surface quality, and the surface quality does not meet the standard; the surface roughness is 0.058μm, and the surface gloss is 716.7GU.
[0181] Application Comparative Example 5:
[0182] The method is basically the same as Application Example 1, except that the titanium alloy polishing liquid prepared in Comparative Example 5 is used to polish the roughly polished titanium alloy workpiece.
[0183] The metallographic microscope image of the polished titanium alloy is as follows: Fig.12 shown.
[0184] The average removal during the first polishing was measured to be 52 mg / 180 s; the surface quality is shown in Fig.12 As shown, it appears mirror-like when observed with the naked eye, and has many white spots when observed under a microscope. The white spots have no obvious effect on the surface quality. Although the surface quality is slightly poor, it basically meets the standard; the surface roughness is 0.137μm and the surface gloss is 739GU.
[0185] The service life of the titanium alloy polishing liquid used in the polishing method was further tested, as shown in Table 1.
[0186] The testing method for service life is: use 2 basically identical titanium alloy TC4 materials for parallel polishing (corresponding to test 1 and test 2 respectively), and record the polishing speed at each time node every 3 hours; among them, 0h corresponds to the polishing speed during the first polishing, 3h corresponds to the polishing speed that can still be achieved at the time node when the polishing liquid has been polishing the same titanium alloy TC4 material for 3 hours, 6h corresponds to the polishing speed that can still be achieved at the time node when the polishing liquid has been polishing the same titanium alloy TC4 material for 6 hours; and so on, until the record is up to 72h.
[0187] In addition, Table 1 records the average values of two parallel polishings (corresponding to Test 1 and Test 2, respectively) at each time point;
[0188] The value corresponding to a 30% decrease in cutting force is a critical point, which means that when the polishing speed drops to this value, it no longer meets the requirements, indicating that a new polishing fluid needs to be replaced. The corresponding time at this time is recorded as the service life of the polishing fluid.
[0189]
[0190] The average values of application examples 1-3 and application comparative example 5 in Table 1 and the values corresponding to a 30% reduction in cutting force are plotted as a life polishing curve. Figures 13 to 16 As shown;
[0191] It can be found that in the 72h test period, the polishing speed of the polishing liquid of application examples 1-3 of the present invention at each time point is always greater than the value corresponding to a 30% decrease in cutting force, indicating that the life of the polishing liquid of application examples 1-3 of the present invention is greater than 72h, especially when it reaches 72h, the polishing speed is still significantly higher than the value corresponding to a 30% decrease in cutting force;
[0192] When the polishing liquid of comparative example 5 reaches 45 hours, the value corresponding to a 30% decrease in cutting force is significantly lower, indicating that the life of the polishing liquid of comparative example 5 can only reach about 45 hours.
[0193] In addition, the polishing quality of the polishing liquids of Comparative Examples 1-4 was poor, so their service life was no longer tested.
[0194] Application Example 4:
[0195] This example provides a mechanical chemical polishing method for titanium alloy, the mechanical chemical polishing method comprising:
[0196] Step (1), grinding and polishing the titanium alloy using a flaky aluminum oxide rough polishing liquid to obtain a rough polished titanium alloy workpiece;
[0197] The titanium alloy is titanium alloy TC4 material;
[0198] The rough polishing liquid for flake alumina is rough polishing liquid A or rough polishing liquid B;
[0199] The rough polishing liquid A is prepared by the following method: ordinary pseudo-boehmite (purchased from Aladdin, measured: Na content: 264ppm, Si content: 394ppm) and ammonium chloride (in terms of mass percentage, the added mass of ammonium chloride is 0.7% of the ordinary pseudo-boehmite) are mixed, and then calcined at 1400°C, and its α-phase conversion rate is monitored during the calcination process until the α-phase conversion rate is ≥99.0%, and then the calcined material is wet-milled (milling beads: spherical zirconium beads, with a diameter of about 3mm), and the median particle size D after ball milling is measured. 50=3.12μm, D97≤9.00μm, appropriately diluted to obtain a flaky alumina slurry with a solid content of 33.3%; 30.0% of the mass of the above flaky alumina slurry is taken as the polishing liquid, 62.2% of deionized water is added and stirred for 20 minutes, 2.7% of aluminum nitrate is added and stirred for 10 minutes, and then 5% of the mass content of the polishing liquid and 8% of the bentonite aqueous solution is added and stirred for 10 minutes; then 0.1% of the mass content of the polishing liquid is added as the polyoxysilane defoamer BYK-024, and stirred for 5 minutes to obtain a rough polishing liquid A;
[0200] The preparation process of coarse polishing liquid B is the same as that of coarse polishing liquid A, the only difference is that the median particle size after ball milling is D50=5.03μm, D97≤15.00μm.
[0201] When the rough polishing liquid A is used as the rough polishing liquid for the flaky alumina, the polishing liquid temperature is 25°C. During the rough polishing process, an oblique axis single-sided polishing machine (model JPX012.2A) is used with a 5-inch American Global LP-66 polyurethane polishing pad to polish the titanium alloy TC4 material. The polishing parameters are as follows: polishing speed 800rpm, polishing time 120s, polishing pressure 0.3MPa;
[0202] When the rough polishing liquid B is used for the flaky alumina, the polishing liquid temperature is 25°C. During the rough polishing process, an inclined axis single-sided polishing machine (model JPX012.2A) is used with a 5-inch American Global LP-66 polyurethane polishing pad to polish the titanium alloy TC4 material. The polishing parameters are: polishing speed 800rpm, polishing time 90s, and polishing pressure 0.3MPa.
[0203] Step (2), grinding and polishing the roughly polished titanium alloy workpiece using a titanium alloy polishing liquid;
[0204] The titanium alloy polishing liquid prepared in Example 4 is used;
[0205] The polishing liquid temperature was 25°C; during the polishing process, an oblique axis polishing machine (model JPX012.2A) was used with a 5-inch polyurethane black damping cloth to polish the titanium alloy TC4 material. The polishing parameters were: polishing speed: 800 rpm, polishing time: 180 s, and polishing pressure: 0.4 MPa.
[0206] Record the average removal amount, surface roughness, surface gloss and visual surface quality.
[0207] Calculation of average removal: Weigh the titanium alloy before and after polishing and calculate the difference, which indicates the strength of the polishing fluid cutting force.
[0208] Surface roughness measurement: measured using a TR-220 handheld surface roughness tester.
[0209] Surface gloss measurement: measured using a BYK AG-4446 60° gloss meter.
[0210] Metallographic microscope image of titanium alloy before polishing Fig.17 (corresponding to the use of coarse polishing liquid A), Fig.18 (corresponding to the use of rough polishing liquid B) as shown. The metallographic microscope image of the polished titanium alloy is as follows Fig.19 (corresponding to the use of coarse polishing liquid A), Fig. 20 (corresponding to the use of coarse polishing liquid B) as shown.
[0211] The solution using rough polishing liquid A: The average removal amount during the first polishing was measured to be 39 mg / 180 s; the surface quality is shown in Fig.19 As shown, it presents a mirror effect when observed with the naked eye, and there are no obvious scratches under microscopic observation, and the surface quality meets the standards; the surface roughness is 0.011μm and the surface gloss is 771.5GU.
[0212] The solution using rough polishing liquid B: the average removal amount during the first polishing was measured to be 42 mg / 180 s; the surface quality is shown in Fig. 20 As shown, it presents a mirror effect when observed with the naked eye, and there are no obvious scratches under microscopic observation, and the surface quality meets the standards; the surface roughness is 0.016μm and the surface gloss is 762.7GU.
[0213] Application Comparative Example 6:
[0214] The method is basically the same as Application Example 4, except that the titanium alloy polishing liquid prepared in Comparative Example 6 is used to polish the roughly polished titanium alloy workpiece.
[0215] Metallographic microscope image of titanium alloy before polishing Fig.21 (corresponding to the use of coarse polishing liquid A), Fig. 22 (corresponding to the use of rough polishing liquid B), the metallographic microscope image of the polished titanium alloy is as follows Fig.23 (corresponding to the use of coarse polishing liquid A), Fig.24 (corresponding to the use of coarse polishing liquid B) as shown.
[0216] The solution using rough polishing liquid A: The average removal amount during the first polishing was measured to be 30 mg / 180 s; the surface quality is shown in Fig.23As shown in the figure, the surface is mirror-like when observed with the naked eye, and there is no obvious scratch under microscopic observation, and the surface quality meets the standard; the surface roughness is 0.014μm, and the surface gloss is 790.1GU. This shows that when the median particle size of the rough polishing liquid is small, a longer polishing time (120s) is used, and the single amorphous alumina polishing liquid used conventionally is used for fine polishing, a relatively good polishing quality can also be achieved.
[0217] The solution using rough polishing liquid B: the average removal amount during the first polishing was measured to be 31 mg / 180 s; the surface quality is shown in Fig.24 As shown in the figure, the surface has a scratched mirror effect when observed with the naked eye, and there are a lot of deep scratches under microscopic observation, and the surface quality does not meet the standard; the surface roughness is 0.196μm, and the surface gloss is 631.9GU. This shows that when the median particle size of the rough polishing liquid is large, a shorter polishing time (90s) is used, and the single amorphous aluminum oxide polishing liquid used conventionally is used for fine polishing, it is impossible to obtain an ideal result in terms of surface quality.
[0218] Therefore, by comparing the above application example 4 and the application comparison example 6, it can be seen that when achieving the same surface quality, the method of the present invention can effectively shorten the time in the rough polishing process by 25%, which can significantly improve production efficiency and reduce production costs.
[0219] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
[0220] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
Claims
1. A mechanical chemical polishing method for titanium alloy, characterized in that: The mechanical chemical polishing method comprises: Step (1), grinding and polishing the titanium alloy with a flaky aluminum oxide rough polishing liquid to obtain a rough polished titanium alloy workpiece; the flaky aluminum oxide rough polishing liquid contains flaky aluminum oxide with a median particle size of 3-8 μm; Step (2), grinding and polishing the roughly polished titanium alloy workpiece using a titanium alloy polishing liquid; The titanium alloy polishing liquid comprises spherical aluminum oxide, flaky aluminum oxide and amorphous aluminum oxide, and the mass ratio of the spherical aluminum oxide, the flaky aluminum oxide and the amorphous aluminum oxide is 1:0.6-2.5:1-4; in the spherical aluminum oxide, α-alumina accounts for more than 99%; in the flaky aluminum oxide, α-alumina accounts for 75%-87%; in the amorphous aluminum oxide, α-alumina accounts for 85%-92%; the median particle size of the spherical aluminum oxide, the median particle size of the flaky aluminum oxide and the median particle size of the amorphous aluminum oxide are each independently 0.8-2.0 μm; Wherein, both the step (1) and the step (2) use an oblique axis polishing machine, and the polishing time of the step (1) is controlled to be less than or equal to 60% of the polishing time of the step (2).
2. The mechanical chemical polishing method of titanium alloy according to claim 1, characterized in that: The polishing time of step (1) is controlled to be less than or equal to 50% of the polishing time of step (2).
3. The mechanical chemical polishing method of titanium alloy according to claim 1, characterized in that: In the step (1) and the step (2), the polishing temperature of the grinding and polishing is controlled to be 15-35°C respectively.
4. The mechanical chemical polishing method of titanium alloy according to claim 1, characterized in that: The grinding and polishing in step (1) is assisted by LP-66 polyurethane polishing pad, and the grinding and polishing in step (2) is assisted by polyurethane black damping cloth.
5. The mechanical chemical polishing method of titanium alloy according to claim 1, characterized in that: During the process of controlling the grinding and polishing, the polishing pressure of the step (1) is less than or equal to the polishing pressure of the step (2).
6. The mechanical chemical polishing method of titanium alloy according to claim 1 or 5, characterized in that: The polishing pressure of the step (1) is controlled to be 0.2-0.4 MPa, and the polishing pressure of the step (2) is controlled to be 0.3-0.5 MPa.
7. The mechanical chemical polishing method of titanium alloy according to claim 1, characterized in that: In the step (1) and the step (2), the polishing speed during the grinding and polishing process is controlled to be 700-900 rpm respectively.
8. The method for mechanical chemical polishing of titanium alloy according to claim 1, characterized in that: The preparation method of the flaky alumina rough polishing liquid comprises: mixing pseudo-boehmite and a mineralizer, then calcining at 1300-1400°C, monitoring the α-phase conversion rate until the α-phase conversion rate is greater than 97%, and then wet-milling the calcined material until the median particle size is 3-8 μm to obtain flaky alumina slurry; mixing the flaky alumina slurry, selective water and a first auxiliary agent to obtain a flaky alumina rough polishing liquid, wherein the first auxiliary agent comprises a combination of one or more selected from aluminum nitrate, citric acid, sodium polycarboxylate, bentonite and a defoaming agent.
9. The method for mechanical chemical polishing of titanium alloy according to claim 1, characterized in that: In the step (2), the absolute value of the difference between any two of the median particle size of the spherical alumina, the median particle size of the flaky alumina, and the median particle size of the amorphous alumina is less than or equal to 0.15 μm.
10. The method for mechanical chemical polishing of titanium alloy according to claim 1, characterized in that: In the step (2), the median particle size of the spherical alumina, the median particle size of the flaky alumina and the median particle size of the amorphous alumina are each independently 1.0-1.6 μm; and / or, in the step (2), the feed mass ratio of the spherical alumina, the flaky alumina and the amorphous alumina is 1:0.8-1.5:1.5-4.
11. The method for mechanical chemical polishing of titanium alloy according to claim 1, characterized in that: In the step (2), in the titanium alloy polishing liquid, the spherical aluminum oxide accounts for 0.60%-1.75%, the flaky aluminum oxide accounts for 0.9%-1.75%, and the amorphous aluminum oxide accounts for 1.5%-2.8%, calculated by mass percentage.
12. The method for mechanical chemical polishing of titanium alloy according to claim 1, characterized in that: In the step (2), the method for preparing the titanium alloy polishing liquid comprises: stirring and mixing the spherical alumina, the flaky alumina and the amorphous alumina with a silane coupling agent respectively, and then mixing them with a second auxiliary agent; wherein the temperature during the stirring and mixing process is controlled to be always less than or equal to 22° C., and the second auxiliary agent comprises a combination of one or more selected from a dispersant, an oxidant, a lubricant, a suspending agent, a defoaming agent and a pH regulator.
13. The method for mechanical chemical polishing of titanium alloy according to claim 12, characterized in that: The ratio of the total added mass of the spherical alumina, the flaky alumina and the amorphous alumina to the added mass of the silane coupling agent is 1:0.008-0.1; and / or, in terms of mass percentage, the silane coupling agent accounts for 0.05%-0.5% in the titanium alloy polishing liquid.
14. The method for mechanical chemical polishing of titanium alloy according to claim 1, characterized in that: In the step (2), the preparation method of the spherical alumina comprises: mixing pseudo-boehmite, sulfuric acid and water into a slurry, spraying and granulating the spherical particles, and then calcining the spherical particles at a calcination temperature of 1030-1200° C., monitoring the α-phase conversion rate until the α-phase conversion rate reaches more than 99%, and then wet ball milling the calcined material to obtain the spherical alumina; In the step (2), the preparation method of the flaky aluminum oxide comprises: mixing pseudo-boehmite and / or aluminum hydroxide and a mineralizer, and then calcining at 1020-1200° C., monitoring the α-phase conversion rate until the α-phase conversion rate reaches 75%-87%, and then wet-ball milling the calcined material to obtain the flaky aluminum oxide; In the step (2), the preparation method of the amorphous alumina comprises: calcining pseudo-boehmite and / or aluminum hydroxide at 1050-1250° C., monitoring the α-phase conversion rate until the α-phase conversion rate reaches 85%-92%, and then wet-ball milling the calcined material to obtain the amorphous alumina.
15. The method for mechanical chemical polishing of titanium alloy according to claim 14, characterized in that: The mineralizer comprises ammonium chloride; and / or, in terms of mass percentage, the amount of the mineralizer added accounts for 0.4%-1.0% of the amount of the pseudo-boehmite and / or aluminum hydroxide added.
16. The method for mechanical chemical polishing of titanium alloy according to claim 1, characterized in that: In the step (2), the method for preparing the titanium alloy polishing liquid comprises: (1) Pseudo-boehmite powder is added to water, and then diluted sulfuric acid with a mass concentration of 10%-25% is added to prepare a slurry, and then spray granulation is performed to obtain spherical particles with a median particle size of 30-80 μm; wherein, in terms of mass percentage, the pseudo-boehmite powder accounts for 40%-50%, water accounts for 49%-59%, and the diluted sulfuric acid accounts for 0.1%-1.0% in the prepared slurry; The spherical particles are calcined at a calcination temperature of 1030-1200° C., and the α-phase conversion rate is monitored until the α-phase conversion rate reaches more than 99%. The calcined material is then wet-milled to a median particle size of 0.8-2.0 μm to obtain a spherical alumina slurry with a solid content of 30%-40%; Pseudo-boehmite and / or aluminum hydroxide and a mineralizer are mixed, and then calcined at 1020-1200° C., and the α-phase conversion rate is monitored until the α-phase conversion rate reaches 75%-87%, and then the calcined material is wet-milled to a median particle size of 0.8-2.0 μm to obtain a flaky alumina slurry with a solid content of 30%-40%; The pseudo-boehmite and / or aluminum hydroxide is calcined at 1050-1250° C., and the α-phase conversion rate thereof is monitored until the α-phase conversion rate reaches 85%-92%. The calcined material is then wet-milled to a median particle size of 0.8-2.0 μm to obtain an amorphous aluminum oxide slurry having a solid content of 30%-40%; (2) mixing and stirring a spherical alumina slurry with a solid content of 30%-40%, a flaky alumina slurry with a solid content of 30%-40%, and an amorphous alumina slurry with a solid content of 30%-40%, adding a silane coupling agent aqueous solution with a mass concentration of 10%-25%, and stirring to obtain a pretreated abrasive slurry; wherein the slurry temperature is kept less than or equal to 22° C. during the stirring process, and the silane coupling agent aqueous solution is obtained by dispersing a silane coupling agent in water; (3) The pretreated abrasive slurry, water and the second auxiliary agent are mixed according to the formula, and the pH value of the system is adjusted to 3.5-7.5 using a pH adjuster to obtain the titanium alloy polishing liquid.
17. A titanium alloy polishing liquid comprising an abrasive and a second auxiliary agent, characterized in that: The abrasive material is composed of spherical aluminum oxide, flaky aluminum oxide and amorphous aluminum oxide; In the spherical alumina, α-alumina accounts for more than 99%; In the flaky aluminum oxide, α-alumina accounts for 75%-87%; In the amorphous alumina, α-alumina accounts for 85%-92%; The mass ratio of the spherical aluminum oxide, the flaky aluminum oxide and the amorphous aluminum oxide is 1:0.6-2.5:1-4; The median particle size of the spherical aluminum oxide, the median particle size of the flaky aluminum oxide, and the median particle size of the amorphous aluminum oxide are each independently 0.8-2.0 μm; Calculated by mass percentage, the titanium alloy polishing liquid contains: 0.60%-1.75% of spherical aluminum oxide, 0.9%-1.75% of flaky aluminum oxide, and 1.5%-2.8% of amorphous aluminum oxide.
18. The titanium alloy polishing liquid according to claim 17, characterized in that: The titanium alloy polishing liquid further comprises, in terms of mass percentage, 0.05%-0.5% of a silane coupling agent, 0.2%-1.5% of a dispersant, 1.0%-2.5% of an oxidant, 0.5%-1.6% of a lubricant, 0.1%-2% of a suspending agent, 0.01%-0.5% of a defoaming agent and 50%-76% of water; The titanium alloy polishing liquid further comprises a pH value adjuster for adjusting the pH value of the titanium alloy polishing liquid to 3.5-7.5.
Citation Information
Patent Citations
Production method of a novel polishing alumina
CN105026315A
Greenness and environmental-protection chemico-mechanical polishing method for nickel alloys
CN109848821A
Aluminum oxide polishing solution for polishing mother pearl shellfish and preparation method of aluminum oxide polishing solution
CN113943534A